Motion analysis of the start phase in breast stroke - Yoshida , T.; Iwahara, F.; Ito, M.; Asami, T. (1999)
In the present study, the start phase of the breaststroke in swimming was analyzed to obtain some insights into the improvements of breaststroke performance. Six male university swimmers participated as subjects. They performed starts with and without stroke and the time when the subject reached 5m was measured. These events were recorded using a high-speed camera system (HSV-500, nac, Japan) at 250fps and an underwater camera (PK1095, Victor, Japan) at 30fps. Nine points which determine eight body segments were digitized and the reaction time, flight angle, entry angle, knee joint angle during block phase and entry distance were measured using motion analysis system (APAS, Ariel Dynamics, USA). The subjects also performed starts in which the timing of the one underwater arm stroke (OUAS) was altered (from 6.0m ~ 9.5m: every 0.5m) and the 15m reaching time was measured.There was a significant positive correlation between the 5m reaching time and the reaction time (r=0.93). Those who took longer time to reach 5m initiate OUAS earlier. The relationship between the 15m reaching times and the timings of OUAS were well fitted using the second order polynomial equations, from which the optimal timing for each subject was yielded. The less the difference between the arbitrary timing and optimal timing of OUAS was, the better the 15m reaching time was (r=0.82). These results will be able to contribute to the improvements of swimming performance, especially for the breaststroke.